Concentration and Potential Sources of Total Gaseous Mercury in a Concentrated Non-Ferrous Metals Smelting Area in Mengzi of China - Xinyu Han; Yuqi Xie; Haojie Su; Wei Du; Guixin Du; Shihan Deng; Jianwu Shi; Senlin Tian; Ping Ning; Feng Xiang; Haitao Xie (Atmosphere)
To investigate concentration and potential sources of total gaseous mercury (TGM) in a concentrated non-ferrous metals smelting area in southwest China, a high temporal resolution automatic mercury meter was used to measure TGM in the environment and the emissions from major sources of Mengzi city. The average concentration of TGM in urban air was 2.1 ± 3.5 ng·m−3 with a range of 0.1~61.1 ng·m−3 over the study period. The highest TGM concentration was in fall (3.3 ± 4.3 ng·m−3). The daytime TGM concentration (2.8 ± 3.5 ng·m−3) was significantly higher than that in the nighttime (1.6 ± 1.1 ng·m−3), which may be attributed to the increased emissions of mercury from the high volume of vehicle activity during the day. To discuss the contributions of local sources and long-range transport, eight pollution events were identified based on the ratio of ΔTGM/ΔCO (Carbon Monoxide), which can be found that local sources are a key contributor to the major TGM pollution events. Concentrations of TGM in flue gases from eight non-ferrous industrial sources were also measured in Mengzi, which were found that the highest TGM emission concentration was up to 4.6 mg·m−3. Simultaneously, the concentrations of TGM in ambient air around these industries and Xidu Tunnel were also detected, the concentrations were 1 to 4 times higher than that in the urban air sampling site. Based on the analysis of air mass and PSCF, when northwest wind happened, these emissions of industries and vehicles can be identified as the primary sources of TGM in urban air of Mengzi.